2014
DOI: 10.5812/numonthly.15278
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Laparoscopic Gonadectomy in a Patient With Complete Androgen Insensitivity Syndrome and Bilateral Sertoli-Leydig Cell Tumor: A Case Report and Brief Review of the Literature

Abstract: Introduction:Complete androgen insensitivity syndrome (previously called testicular feminization) is specified by a 46 XY karyotype and negative sex chromatin, bilateral undescended testes, female genitalia appearance, and lack of mullerian derivatives.Case Presentation:A 28-year-old woman with complete (severe) androgen resistance underwent prophylactic laparoscopic bilateral gonadectomy because of the eventually increased risk of gonadal malignancy. Although the gonads appeared grossly normal, microscopic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
12
0
4
Order By: Relevance
“…Our review of the literature revealed 29 previously published cases of bilateral ovarian SLCT (Tables 1 and 2) 14,19–42 ; two of these are included in this study (cases 2 and 3 in Table 1). Where possible, the articles and the photomicrographs were reviewed to try to determine the type of SLCT; this was sometimes difficult, given a paucity of pathological description and photomicrographs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature revealed 29 previously published cases of bilateral ovarian SLCT (Tables 1 and 2) 14,19–42 ; two of these are included in this study (cases 2 and 3 in Table 1). Where possible, the articles and the photomicrographs were reviewed to try to determine the type of SLCT; this was sometimes difficult, given a paucity of pathological description and photomicrographs.…”
Section: Resultsmentioning
confidence: 99%
“…has reviewed the photomicrographs for those two reported cases. We feel that one of these does represent well‐differentiated SLCT (case 11 in Table 2), 27 but we feel that the other (case 20 in Table 2), 33 which occurred in a patient with complete androgen insensitivity syndrome and a 46XY karyotype, represents the hamartomas/Sertoli cell adenomas that occur in the gonads in this condition. In a recent study from our group, we showed that moderately and poorly differentiated SLCTs (including retiform variants and those with heterologous elements) were commonly associated with DICER1 mutations (all 30 cases in that study) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…La tumeur à cellules de Sertoli-Leydig est une tumeur rare du cordon sexuel et de stroma qui représente moins de 1% de l'ensemble des tumeurs ovariennes, survenant souvent à un âge jeune. Elle est également rarement développée chez le patient avec syndrome d'ISCA, il n'existe que deux cas rapportés dans la littérature [ 1 ]. Les tumeurs bénignes, bien différenciées représentent 10% de l'ensemble des tumeurs à cellules de Sertoli-Leydig et sont souvent associées au syndrome de testicule féminisant [ 11 ], c'est le cas de notre deuxième observation.…”
Section: Discussionunclassified
“…Le syndrome de résistance complète aux androgènes (SICA) ou anciennement appelé testicule féminisant (TF) est une affection rare qui correspond à la forme complète des pseudohermaphrodismes androgynoïdes. C'est une maladie génétiquement déterminée récessive liée à l'X, en rapport avec des mutations au niveau de Xq11-q12 des gènes du récepteur des androgènes [ 1 ]. Elle est caractérisée par un trouble de la réceptivité périphérique aux androgènes secrétés par les testicules.…”
Section: Introductionunclassified
See 1 more Smart Citation